Salinity and Temperature Regimes in Eastern Alaskan Beaufort Sea Lagoons in Relation to Source Water Contributions - Harris, Carolynn M.; McClelland, James W.; Connelly, Tara L.; Crump, Byron C.; Dunton, Kenneth H. (Estuaries and coasts)
Shallow estuarine lagoons characterize >70 % of the eastern Alaskan Beaufort Sea coastline and, like temperate and tropical lagoons, support diverse and productive biological communities. These lagoons experience large variations in temperature (-2 to 14 °C) and salinity (0 to >45) throughout the year. Unlike lower latitude coastal systems, transitions between seasons are physically extreme and event-driven. On Arctic coastlines, a brief summer open-water period is followed by a 9-month ice-covered period that concludes with a late-spring sea ice breakup and intense freshwater run-off. From 2011 to 2014, we examined interannual variations in water column physical structure (temperature, salinity, and δ¹⁸O) in five lagoons that differ with respect to their degree of exchange with adjacent marine waters and magnitude of freshwater inputs. Temperature, salinity, and source water composition (calculated using a salinity and δ¹⁸O mixing model) were variable in space and time. During sea ice breakup in June, water column δ¹⁸O and salinity measurements showed that low salinity waters originated from meteoric inputs (50-80 %; which include river inputs and direct precipitation) and sea ice melt (18-51 %). Following breakup, polar marine waters became prevalent within a mixed water column over the summer open-water period within all five lagoons (26-63 %). At the peak of ice-cover extent and thickness in April, marine water sources dominated (75-87 %) and hypersaline conditions developed in some lagoons. Seasonal runoff dynamics and differences in lagoon geomorphology (i.e., connectivity to the Beaufort Sea) are considered key potential drivers of observed salinity and source water variations.